Forestry Building interior showing portion of the Washington Forestry Exhibit, Alaska Yukon Pacific Exposition, Seattle, Washington, 1909 - Nowell, Frank H., 1864-1950 (1909)
Caption on image: x2262 PH Coll 727.359 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number